2016
DOI: 10.18632/oncotarget.13108
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of C5a-C5aR axis predicts poor postoperative prognosis of patients with clear cell renal cell carcinoma

Abstract: Anaphylatoxin C5a and its receptor C5aR on cancer cells constitute a vital axis to cancer progression. In this study, we measured C5aR level by immunohistochemistry in the same cohort of our previous C5a research, and C5a-C5aR axis status was determined by synthesizing C5a and C5aR data. C5aR was an adverse independent prognostic factor for ccRCC patients. Kaplan-Meier analyses revealed the unique position of both C5a and C5aR high population in postoperative survival, based on which patients were then shunted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…Taken together, our results in ccRCC and in the mouse model demonstrated that classical complement pathway activation occurs in cancer and has a pro-tumoral effect. Our data fit with the findings that positive C5a/C5aR staining is associated with a poor prognosis in ccRCC (48,49)…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, our results in ccRCC and in the mouse model demonstrated that classical complement pathway activation occurs in cancer and has a pro-tumoral effect. Our data fit with the findings that positive C5a/C5aR staining is associated with a poor prognosis in ccRCC (48,49)…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the used antibodies did not allow to determine the exact nature of the fragments, the anti-C3d recognizing C3, C3b, iC3b as well as the C3dg and C3d fragments, each having different function. In another cohort, though, the C5a-positive staining (marking indistinguishably the presence of the anaphylatoxin C5a and the intact C5) and the presence of C5aR+ staining were correlated with poor prognosis 96,97 . The malignant cells in KIRC, therefore, hijack macrophage-produced C1q to complement the remaining components made by the cancer cell, to promote tumor growth.…”
Section: Cancers With "Protective C3"mentioning
confidence: 92%
“…More and more evidence has shown that C5aR is found in tumor cells of various common cancers. The survival rate of patients with C5aR positive or highly expressed nonsmall cell lung cancer 14 , breast cancer, transparent cell kidney cancer 15 , gastric cancer and other patients is lower than that of corresponding patients with C5aR1 negative. A variety of cancer cells have abnormal expression of C5aR in different organs, specific binding of C5a and C5aR, activation of downstream pathways, enhancement of the mobility of cancer cells, secretion of matrix metalloproteinase (MMP) and other beneficial processes of cancer cells.…”
Section: C5a and Tumor Formationmentioning
confidence: 87%